The link between immune thrombocytopenia and the cytokine profile: a bridge to new therapeutical targets - Andreescu, Mihaela (Frontiers in Hematology, 2023)
Immune thrombocytopenia (ITP) is manifested by depleted platelet reserves primarily due to the immune-mediated destruction of platelets. The pathogenesis of ITP is complex and involves dysregulation of the immune system. This review aimed to summarize the current knowledge on the cytokine profile in ITP and its potential implications for diagnosis, treatment, and prognosis. Several studies have reported that ITP patients have an altered cytokine profile compared to healthy individuals. Specifically, there is evidence of an imbalance of pro-inflammatory (IL-6, TNF-α, IFNγ) and anti-inflammatory cytokines (IL-10, TGF-β). The cytokine profile in ITP appears to be heterogeneous, with different patterns observed in different subsets of patients. For example, some studies have reported a Th1-type cytokine profile, characterized by elevated levels of IFN-γ and TNF-α, while others have reported a Th2-type cytokine profile, characterized by elevated levels of IL-4 and IL-10. There is also evidence of a shift from a Th1 to a Th2 cytokine profile in some patients over time. The cytokine profile in ITP may have important implications for diagnosis, treatment, and prognosis. Targeting specific cytokines or cytokine pathways may also represent a promising therapeutic approach for ITP. Further studies are needed to better understand the heterogeneity of the cytokine profile in ITP and its potential implications for clinical management.